Effectiveness of STEM-Based Differentiated Learning in Enhancing Elementary Students' Critical Thinking Skills - Dewi Kristyowening; Idam Ragil Widianto Atmojo; Matsuri Matsuri (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2025)
Developing critical thinking is essential in contemporary schooling to prepare students to analyze, evaluate, and solve complex problems. This study examined the effectiveness of STEM-based differentiated instruction in enhancing the critical thinking of elementary students. A quasi-experimental design assigned intact classes to an experimental group receiving STEM-differentiated lessons and a control group receiving traditional cooperative instruction. Critical thinking was assessed through essay-type pretests and posttests, which were aligned with analytic rubrics. Independent t-tests revealed significantly greater gains for the experimental group compared to the control (t = 11.76, p = 1.99 × 10−17). N-Gain analysis revealed a moderate improvement in the experimental group (0.47) compared to a low improvement in the control group (0.19). These results suggest that integrating differentiation strategies—readiness-based tasks, choice of process and product, and flexible grouping—within STEM contexts strengthens conceptual understanding, increases cognitive engagement, and fosters inquiry-driven exploration tailored to individual needs. The findings support the pedagogical value of STEM-based differentiated instruction for cultivating higher-order thinking in the elementary grades. Practical implications include sustained teacher professional development, curriculum resources that enable tiered tasks and authentic problems, and supportive scheduling to facilitate iterative design and reflection. Future research should examine longer-term retention, classroom implementation fidelity, and differential effects across student subgroups.